Pengaruh Siaran Langsung dan Kemudahan Terhadap Minat Beli Mahasiswa UCIC Pada Platform TikTok Shop - Mulyandani, Nur'aeni; Wulandani, Oryz Agnu Dian (Forum Kerjasama Pendidikan Tinggi, 2024)
Competition in the business world is currently getting tighter with technological developments which have resulted in business people carrying out digital promotion strategies with live broadcasts through the TikTok platform in order to attract consumers to buy products. Therefore, this study was conducted to determine and analyze the effect of live broadcasts, and the ease of shopping on the TikTok Shop platform on the buying interest of UCIC students. This research uses quantitative methods and the data collection process is carried out using online questionnaire distribution. The sampling method in this study was non-probability purposive sampling, so that a sample of 100 respondents was formed. The data analysis method in this study used Smart PLS 4.1. The results of this study indicate that live broadcast and convenience have a positive and significant effect on the purchase intention of UCIC students on the TikTok Shop platform.